Electrochemical construction of a bio-inspired micro/nano-textured structure with cell-sized microhole arrays on biomedical titanium to enhance bioactivity. (20th August 2015) - Liang, Jianhe; Song, Ran; Huang, Qiaoling; Yang, Yun; Lin, Longxiang; Zhang, Yanmei; Jiang, Pinliang; Duan, Hongping; Dong, Xiang; Lin, Changjian
Graphical abstract: Highlights: The bio-inspired structure mimicked mulit-level structures of natural bone. Ordered cell-sized microhole arrays were employed as microscale structure. High surface roughness and superhydrophilicity were achieved on the titanium surface. The bio-inspired titanium surface showed superior ability of biomineralization. Cell responses were enhanced on the bio-inspired micro/nano-texutred surface. Abstract: Biomimetic surface design of medical implants is vitally crucial to improve cellular responses and the integration of tissue onto materials. In this study, a novel hierarchical cell-sized microhole array combined with a nano-network structure was fabricated on a medical titanium surface to mimic multi-level bone structure. A three-step procedure was developed as follows: 1) electrochemical self-organization of etching on titanium substrate to create highly ordered cell-sized microhole arrays, 2) suitable dual acid etching to increase the roughness of the microholes, and then 3) electrochemical anodization in a NaOH electrolyte to construct a nano-network porous titania layer on the above micro-roughened surface. The bio-inspired micro/nano-textured structure presented the enhanced wettability and superhydrophilicity. The ability of in vitro biomineralization and corrosion resistance of the bio-inspired micro/nano-textured structure were enhanced after annealing treatment. More importantly, the bio-inspired micro/nano-textured structure on the titanium surface possessed a favourable interfacial environment to enhance attachment and proliferation of human osteoblast-like MG63 cells. All of the results demonstrated that such a bio-inspired surface of micro/nano-textured porous TiO2 is a most promising candidate for the next generation of titanium implants.